Identification of partial resistant genotypes of Indian mustard against Alternaria brassicicola under late sown condition in Bihar - Matlooba Naseem; Chanda Kushwaha; Abhijeet Ghatak; JN Srivastava; Chandan Kishore; Saurabh Bharti (Journal of Oilseed Brassica, 2026)
The present investigation was undertaken to identify the partial resistant sources to Alternaria blight (Alternariabrassicicola) in Indian mustard under late sown environmental conditions. Fifteen genotypes of Indian mustard wereevaluated in split plot design under artificial inoculation at four different dates of sowing during Rabi season, 2019-20(12th Nov, 19th Nov, 26th Nov and 3rd Dec). The data obtained from study show the significant effect of date of sowing onpercent disease index and area under disease progress curve (AUDPC) under late sown condition due to early onset ofdiseases at early growth stages coupled with warmer environmental condition. Among different genotypes of Indianmustard, BRRM-101, BRRM-102, BRRM-103, BRRM-104, BRRM-106 line shows less percent disease index as well asarea under the disease progress curve.